Requirements for ER‐Arrest and Sequential Exit to the Golgi of Tomato Spotted Wilt Virus Glycoproteins - Ribeiro, Daniela; Goldbach, Rob; Kormelink, Richard (Traffic (Copenhagen, Denmark), 2009)
The envelope glycoproteins Gn and Gc are major determinants in the assembly of Tomato spotted wilt virus (TSWV) particles at the Golgi complex. In this article, the ER‐arrest of singly expressed Gc and the transport of both glycoproteins to the Golgi upon co‐expression have been analyzed. While preliminary results suggest that the arrest of Gc at the ER (endoplasmic reticulum) did not appear to result from improper folding, transient expression of chimeric Gc, in which the transmembrane domain (TMD) and/or cytoplasmic tail (CT) were swapped for those from Gn, showed that the TMD of Gn was sufficient to allow ER‐exit and transport to the Golgi. Expression of both glycoproteins in the presence of overexpressed Sar1p‐specific guanosine nucleotide exchange factor Sec 12p, resulted in ER‐retention demonstrating that the viral glycoproteins are transported to the Golgi in a COPII (coat protein II)‐dependent manner. Inhibition of ER‐Golgi transport by brefeldin A (BFA) had a similar effect on the localization of Gn. However, inhibition of ER (endoplasmic reticulum) to Golgi transport of co‐expressed Gc and Gn by overexpression of Sec 12p or by BFA revealed distinct localization patterns, i.e. diffuse ER localization versus concentration at specific spots.